2021
DOI: 10.1186/s13690-021-00733-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its associated factors among married women in 19 sub-Saharan African countries

Abstract: Background Sub-Saharan Africa (SSA) remains the region with the highest burden of anemia globally. Since anemia has both health and non-health-related consequences, its reduction is one of the Sustainable Development Goals. Therefore, this study aimed to examine the prevalence of anemia and its associated factors among married women in SSA. Methods Using Stata version-14 software, the analysis was done on 89,029 married women from the Demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
4
16
1
Order By: Relevance
“…Pregnant women whose husbands/partners had primary or no formal education were less likely to be anaemic in this study. In reality, this is contrary to what is expected, for example, studies conducted in Nepal, India and sub-Saharan Africa [51][52][53] found that women whose husbands/partners had a higher education level were less likely to be affected by anaemia during pregnancy. The observed pattern, however, may be due to misinformation and perceptions about taking iron supplements during pregnancy, especially among the educated.…”
Section: Discussionmentioning
confidence: 60%
“…Pregnant women whose husbands/partners had primary or no formal education were less likely to be anaemic in this study. In reality, this is contrary to what is expected, for example, studies conducted in Nepal, India and sub-Saharan Africa [51][52][53] found that women whose husbands/partners had a higher education level were less likely to be affected by anaemia during pregnancy. The observed pattern, however, may be due to misinformation and perceptions about taking iron supplements during pregnancy, especially among the educated.…”
Section: Discussionmentioning
confidence: 60%
“…19 The two primary confounders we expected to influence the relationship between occupation and Hgb were nutrition and socioeconomic status. We accounted for these major confounders using body mass index, marital status, and religion (which can influence diet) for the former, [20][21][22] and marital status, wealth index, educational level, and cluster agricultural percentage for the latter. 23 Through IPUMS-DHS, we extracted data on male workers' occupation, altitude-adjusted Hgb, age, body mass index, wealth index, education level, marital status, religion, and cluster agricultural percentage.…”
Section: Exposure Outcome and Confoundersmentioning
confidence: 99%
“…Anaemia is responsible for significant morbidity and mortality in Africa and while it is not high on the list of main global health concerns, 12 in less developed countries can contribute unnecessarily and greatly to the depletion of already strained resources and increase the overall burden of disease. 13 Although numerous studies have been carried out on the prevalence and effect of anaemia on the morbidity and mortality of pregnant women, non-pregnant women and children, relevant data to determine the prevalence of anaemia in other populations such as adolescents, men and the elderly are limited. 14 Research has shown that anaemia is concentrated in low socioeconomic groups and that there is a strong correlation between the overall economic status of a country and the prevalence of anaemia.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Anemia is responsible for significant morbidity and mortality in Africa and while it is not high on the list of the main global health concerns, 12 in less developed countries, it can contribute unnecessarily and greatly to the depletion of already strained resources and increase the overall burden of disease. 13 …”
Section: Introductionmentioning
confidence: 99%